Activation of autophagy reverses progressive and deleterious protein aggregation in PRPF31 patient‐induced pluripotent stem cell‐derived retinal pigment epithelium cells. Issue 3 (16th March 2022) - Georgiou, Maria; Yang, Chunbo; Atkinson, Robert; Pan, Kuan‐Ting; Buskin, Adriana; Molina, Marina Moya; Collin, Joseph; Al‐Aama, Jumana; Goertler, Franziska; Ludwig, Sebastian E. J.; Davey, Tracey; Lührmann, Reinhard; et al.
Abstract: Introduction: Mutations in pre‐mRNA processing factor 31 ( PRPF31 ), a core protein of the spliceosomal tri‐snRNP complex, cause autosomal‐dominant retinitis pigmentosa (adRP). It has remained an enigma why mutations in ubiquitously expressed tri‐snRNP proteins result in retina‐specific disorders, and so far, the underlying mechanism of splicing factors‐related RP is poorly understood. Methods: We used the induced pluripotent stem cell (iPSC) technology to generate retinal organoids and RPE models from four patients with severe and very severe PRPF31‐adRP, unaffected individuals and a CRISPR/Cas9 isogenic control. Results: To fully assess the impacts of PRPF31 mutations, quantitative proteomics analyses of retinal organoids and RPE cells were carried out showing RNA splicing, autophagy and lysosome, unfolded protein response (UPR) and visual cycle‐related pathways to be significantly affected. Strikingly, the patient‐derived RPE and retinal cells were characterised by the presence of large amounts of cytoplasmic aggregates containing the mutant PRPF31 and misfolded, ubiquitin‐conjugated proteins including key visual cycle and other RP‐linked tri‐snRNP proteins, which accumulated progressively with time. The mutant PRPF31 variant was not incorporated into splicing complexes, but reduction of PRPF31 wild‐type levels led to tri‐snRNP assembly defects in Cajal bodies of PRPF31 patient retinal cells, altered morphology of nuclear speckles and reduced formation of active spliceosomes giving rise to global splicing dysregulation. Moreover, the impaired waste disposal mechanisms further exacerbated aggregate formation, and targeting these by activating the autophagy pathway using Rapamycin reduced cytoplasmic aggregates, leading to improved cell survival. Conclusions: Our data demonstrate that it is the progressive aggregate accumulation that overburdens the waste disposal machinery rather than direct PRPF31‐initiated mis‐splicing, and thus relieving the RPE cells from insoluble cytoplasmic aggregates presents a novel therapeutic strategy that can be combined with gene therapy studies to fully restore RPE and retinal cell function in PRPF31‐adRP patients. Abstract : Schematic presentation shows the localisation of mutant PRPF31 in the cytoplasm of RP11‐RPE cells and accumulation of aggregates containing HSPs, visual cycle and ubiquitin conjugated proteins, which were much reduced upon application of autophagy activator, Rapamycin. m‐mutant PRPF31, CB‐Cajal bodies, Ub‐ubiquitin, HSPs‐heat shock proteins.